Checklist for safe cardiac surgery: integrative review (Research, Society and Development, 2021)
Objective: to identify a checklist for safe cardiac surgery in the literature. Methodology: this is an integrative review, consisting of six stages, carried out in Medline databases via Pubmed (National Library of Medicine, National Institutes of Health), Cinhal (Cumulative Index to Nursing and Allied Health Literature), Lilacs (Latin American Literature and of the Caribbean in Health Sciences), Scopus and Web of Scienc, between September and October 2020. Results: the search resulted in eight articles that presented a checklist for cardiac surgery. As for the origin of the studies, most were from the United States of America (USA), 50%, in relation to the professionals who were part of the instruments, anesthetist, surgeon, perfusionist, nurse and scrub nurse were included. lists and in the surgical phase the most prevalent was Time out. Conclusion: it was possible to verify in the literature the existence of a checklist for safe cardiac surgery with evidence that brings together verification elements for the safety of cardiac patients.